Measuring technology-facilitated sexual violence and abuse: a scoping review protocol of existing measurements - Caroline Bradbury-Jones; Pui Hing Chau; Edmond Pui Hang Choi; Sharon Hoi Lam Pak; Chanchan Wu (BMJ Open, 2024)
Introduction Technology-facilitated sexual violence and abuse (TFSVA) refers to a range of behaviours in which digital technologies are used to facilitate both virtual and face-to-face sexual harm. The proliferation of smartphone usage and increasing internet penetration rates across the world have made it easier for individuals to become perpetrators and victims of TFSVA. Since empirical studies of TFSVA remain limited in the academic arena, and there is an absence of evidence to support the development of a standardised TFSVA measurement, this review aims to explore what TFSVA measurements are currently available and their potential use in measuring TFSVA.Methods and analysis This scoping review will be structured according to the Joanna Briggs Institute recommended framework. Keywords related to ‘technology’, ‘sexual violence’ and ‘measure’ will be used. Any paper related to measurements of TFSVA will be included without limitation to any population or setting. A search will be conducted from database inception until May 2024 for published literature in English and Chinese electronic databases, which included PubMed, Embase, CINAHL, Scopus, ProQuest, Web of Science, Chinese National Knowledge Infrastructure, SinoMed, Index to Taiwan Periodical Literature and Ariti Library. Screening and study selection will be conducted by two independent reviewers. Data will be extracted and reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews Checklist. The PAGER (Patterns, Advances, Gaps, Evidence for practice and Research recommendations) Framework will be used to report the findings.Ethics and dissemination Since the scoping review methodology consists of reviewing and collecting data from publicly available materials, this study does not require ethics approval. This scoping review has the potential to serve as the most appropriate way to explore existing evidence related to this emerging phenomenon. The results of this review are expected to highlight various types of TFSVA measurement developed in different settings. Further work is required to develop measurements adapted for specific populations and tested to ensure acceptability and cultural competence. The results will be disseminated through a peer-reviewed publication and conference presentations.Review registration The protocol of this review was registered within the Open Science Framework (https://doi.org/10.17605/OSF.IO/Q5ETW) on 13 March 2024.